Phonon Raman scattering in LaMn1-xCoxO3 (x = 0, 0.2, 0.3, 0.4, and 1.0) - Gnezdilov, V.P.; Pashkevich, Yu.G.; Yeremenko, A.V.; Lemmens, P.; Guntherodt, G.; Shiryaev, S.V.; Bychkov, G.L.; Barilo, S.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The Raman-active phonons in perovskite-like LaMn1–xCoxO3 (x = 0, 0.2, 0.3, 0.4, and 1.0) were studied by measuring Raman spectra at temperatures of 295 and 5 K. The changes in the spectra with Co doping are correlated with the decrease of orthorhombic distortions. Surprisingly more phonon lines than allowed for the rhombohedral LaCoO3 structure were observed.